A comparison of postoperative pain after transumbilical single‐port access and conventional three‐port total laparoscopic hysterectomy: a randomized controlled trial. (28th September 2015) - Chung, Ji‐Hyun; Baek, Jong Min; Chung, Kyudon; Park, Eun Kyung; Jeung, In Cheul; Chang, Hyun Tae; Choi, Ji Hyang; Kim, Chan Joo; Lee, Yong Seok
Abstract: Introduction: The objective of this study was to compare postoperative pain between single‐port access total laparoscopic hysterectomy (SPA‐TLH) using a transumbilical single‐port system and conventional multi (three)‐port access total laparoscopic hysterectomy (MPA‐TLH). Material and methods: A randomized controlled trial was conducted on 60 women who underwent SPA‐TLH and MPA‐TLH for benign gynecologic diseases between March 2014 and January 2015. Patients were randomly assigned to undergo SPA‐TLH ( n = 30) or MPA‐TLH ( n = 30). The variables measured included surgical outcomes and postoperative pain at 30 min and 1, 12, 24, and 48 h after surgery, assessed by the visual analog scale, bolus requirement of intravenous patient‐controlled analgesia, and additional analgesic use. Results: The two study groups did not differ in terms of patient demographics or surgical outcomes except for operative time. The SPA‐TLH group had a longer operative time ( p < 0.0001) compared with the MPA‐TLH groups. There were no differences in pain scores between the two groups. The SPA‐TLH group had significantly more intravenous analgesia requests during the 12–24 h after surgery (2.17 ± 3.05 vs. 0.79 ± 1.99; p = 0.047), more 24–48 h postoperative analgesics (0.21 ± 0.41 vs. 0.03 ± 0.19; p = 0.045), and more total additional analgesics (0.97 ± 0.94 vs. 0.45 ± 0.87; p = 0.034). Conclusion: SPA‐TLH was feasible compared with MPA‐TLH but the SPA‐TLH group had a longer operative time. Although there is no difference in pain based on the visual analog scale pain score, the SPA‐TLH group required more analgesia to give the same postoperative pain control.